Makna Ritual Pengobatan Tari Longkap-Longkap dalam Aspek Seni Pertunjukan - Silviani Silviani (Fakultas Bahasa dan Seni UNP, 2022)
AbstractThe Longkap-Longkap dance is a ritual dance that is functioned as a means of treatment by the Sakai tribal community in Bengkalis Regency, Muara Basung Village. The existence of the Longkap-Longkap dance that is still alive in the Sakai tribal community is a combination of customs, beliefs, and norms that have been inherited by their ancestors. Their defense of an ancestral tradition is an embodiment of culture which is expressed through symbols, meanings, and values in the Longkap-longkap dance. This research is a type of qualitative research using a phenomenological approach derived from field data sources and literature. The results of the research found describe the life of the Sakai people and the way of treatment carried out by the Sakai people through a dance to cure diseases. The beauty that is seen in the form of dance movements, treatment methods, and the socio-culture of the Sakai tribal community makes this culture a form of expressing identity that is unique to minority groups.